THE ALGORITHM FOR SOLVING THE PROBLEM CONTACT OF THE WHEEL SAND RAILS - Savchuk, O. M.; Reidemeister, O. H.; Savchenko, K. B.; Shykunov, O. O. (Science and Transport Progress, 2006)
The algorithm of decision of contact task of power co-operation of the pair «wheel–rail» is resulted in the modern raising for the detailed mathematical design of wheel and rail by the method of finite elements.